THE EFFECTS OF SPOUSAL VIOLENCE ON SPOUSES DURING COVID-19 LOCKDOWN IN MAKURDI METROPOLIS OF BENUE STATE - Terver Anyo, Stephen; Onyemowo Ortyom, Juliana (African Journal of Social and Behavioural Sciences, 2024)
One of the significant social issues affecting families recently is spousal violence (SV). Lockdowns are noted to have triggered spousal violence globally at an alarming rate. This study examined the rate of spousal violence during the COVID-19 lockdown in Makurdi metropolis, assessed the effects of COVID-19 lockdown and spousal violence among households in Makurdi metropolis of Benue State, Nigeria and suggested ways on how household members can mitigate spousal violence. The study was anchored on Anomie’. A cross-sectional survey research design was employed for this study. The study population was comprised of members of households, specifically adult males and females aged 18 and above, married, and residents of Makurdi Metropolis. The sample size of this study was determined using Cochran’s (1977) formula. Questionnaire and key informant interview methods were used for data collection, and data was analysed both quantitatively and qualitatively. The study’s findings revealed that the COVID-19 lockdown created a breeding ground for spousal violence during the lockdown period. Findings further revealed that the rate of spousal violence during COVID-19 increased. The effects of spousal violence were social, psychological, economic and physical. The study concluded that spousal violence has impacted negatively on the wellbeing of spousal relationships. The study, therefore, recommended that counsellors should encourage spouses to have a mutual understanding among them in order to foster family unity and progress. Awareness or sensitisation should be made public so that victims of spousal violence can easily access services on physical assault.